213k views
0 votes
45 POINTS h(x) = 1/x+2 and k(x) = 3x - 4
h[k(x)] =

User Stratton
by
5.3k points

2 Answers

4 votes
.............................
45 POINTS h(x) = 1/x+2 and k(x) = 3x - 4 h[k(x)] =-example-1
User Barth
by
5.4k points
2 votes

We are told that h(x) = 1 / (x+2) and k(x) = 3x - 4. We want to find h(k(x)), or (h o k)(x). We work INSIDE OUT.

h(k(x)) = h(3x - 4).

Now we take the function, 3x - 4, and apply what h(x) wants us to do.

Evaluating h(3x - 4) means that we put the 3x - 4 into h(x).

h(x) = 1 / (x+2)

So h(3x -4) = 1 / (3x -4) + 2 <---- notice how x was the same. so are the 3x -4 parts

= 1 / 3x - 2


Thus, the composition is
(1)/(3x-2)

User Vinson
by
6.0k points